Censor Nikolay Ratynsky’s Role in Russian Journalism of the Second Half of the 19th Century - Mazalevskiy, Dmitriy (Slavica, 2018)
Recently, the political climate in Russia has caused the question of censorship to become an increasingly relevant issue, the history of which is necessary to explore and understand. The prevailing view regarding censorship is that it is a tool used to suppress the freedom of speech by stifling the writer’s thoughts. However, there were some eminent censors such as the poet Fyodor Tyutchev and the writer Ivan Goncharov. In this regard, it has become commont to consider censorship isolated from any moral categories and interpret g it only as a professional activity. In this context, the work of the censor Nikolai Ratynsky is of particular interest to us. Until now, little has been published on his influence as a censor on the writers of his time on the high professional level of his work in this capacity. Most of the corrections Ratynsky made were valid and justified by the political situation in the Russian Empire. He himself is further proof that, along with Tyutchev and Goncharov, there were honorable and qualified men among the censors of the time. All this allows us to claim that it is necessary to objectively consider and study the work of censors and ignor preconceptions and stereotypes that are usually associated with the word censor.